2021
DOI: 10.1111/ijd.15632
|View full text |Cite
|
Sign up to set email alerts
|

International registry of dermatological manifestations secondary to COVID‐19 infection in 347 Hispanic patients from 25 countries

Abstract: Background The infection by coronavirus disease 2019 (COVID‐19) has been associated with multiple cutaneous manifestations, although characterization of them in Hispanic patients with darker skin phototypes is lacking. The objective of this study is to characterize the clinical dermatological manifestations associated with COVID‐19 infection in cases with few or without general symptoms in patients from Latin America. Methods Cross‐sectional study using a questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
4
0
3
Order By: Relevance
“…High levels of CXCL10 were found in the sera of patients affected by PR in a study conducted by Drago et al in 2015 15 and in sera of SARS‐CoV2 subjects 2 . In addition, Ocampo‐Candiani et al suggest that the hypercytokinemia and expression of IFN‐inducible genes during SARS‐CoV‐2 infection could explain the onset of cutaneous manifestations in symptomatic patients of COVID‐19 infection, through the overexpression of genes involved in inflammation 32 . Lastly, Gallman et al reported an increased expression of type I IFN‐induced genes in the skin biopsies of chilblain lesions in COVID‐19 patients, and many other studies have proposed that COVID‐19‐associated chilblains and other cutaneous manifestations may be the result of an overactive type I IFN response 4 .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…High levels of CXCL10 were found in the sera of patients affected by PR in a study conducted by Drago et al in 2015 15 and in sera of SARS‐CoV2 subjects 2 . In addition, Ocampo‐Candiani et al suggest that the hypercytokinemia and expression of IFN‐inducible genes during SARS‐CoV‐2 infection could explain the onset of cutaneous manifestations in symptomatic patients of COVID‐19 infection, through the overexpression of genes involved in inflammation 32 . Lastly, Gallman et al reported an increased expression of type I IFN‐induced genes in the skin biopsies of chilblain lesions in COVID‐19 patients, and many other studies have proposed that COVID‐19‐associated chilblains and other cutaneous manifestations may be the result of an overactive type I IFN response 4 .…”
Section: Resultsmentioning
confidence: 97%
“… 2 In addition, Ocampo‐Candiani et al suggest that the hypercytokinemia and expression of IFN‐inducible genes during SARS‐CoV‐2 infection could explain the onset of cutaneous manifestations in symptomatic patients of COVID‐19 infection, through the overexpression of genes involved in inflammation. 32 Lastly, Gallman et al reported an increased expression of type I IFN‐induced genes in the skin biopsies of chilblain lesions in COVID‐19 patients, and many other studies have proposed that COVID‐19‐associated chilblains and other cutaneous manifestations may be the result of an overactive type I IFN response. 4 Murdaca et al reported that inflammatory components during viral infections, such as SARS‐CoV and MERS, activate transcriptionally regulated genes in endothelial cells, including NF‐κB binding sites in their promoter regions, and gene analysis performed exerting mutations demonstrated the pivotal role of NF‐κB in the expression of pro‐inflammatory genes.…”
Section: Resultsmentioning
confidence: 99%
“…publicaron los resultados de un registro de manifestaciones dermatológicas secundarias a la infección por COVID-19 en 347 pacientes hispanos de 25 países (Latinoamérica-España). Hasta el momento, ese trabajo constituye la serie más importante en nuestra región, y describe por primera vez el prurito y la disestesia palmoplantar como síntomas 15 . Comparativamente, en el presente trabajo, los 83 casos descriptos pertenecen a la Provincia de Buenos Aires (Argentina), lo cual constituye una gran fortaleza metodológica debido al tamaño de la muestra analizada.…”
Section: Discussionunclassified
“…La Dirección de Educación Médica del Colegio, con el Dr. Fernando Gatti al frente, fue fundamental en el éxito y promoción de estas acciones. Pero también sirvió para unirnos y realizar estudios multicéntricos sobre los efectos de la COVID-19 en la piel, que vieron la luz en una publicación internacional 6 . Celebramos el primer congreso virtual del CILAD en 2020, con gran éxito de asistencia y con ponentes internacionales de todos los rincones del mundo, que, de forma magistral y generosa, divulgaron los últimos conocimientos en nuestra especialidad.…”
Section: Editorialunclassified